Modified fourth generation autologous cartilage transplantation for grade 2-3 knee osteoarthritis - Sundaram, Nandkumar; Tinnanur Sekar, Deepanand; Sakthivel, Sreedharshaa; Prasath, Arun (International Journal of Research in Medical Sciences, 2026)
Osteoarthritis (OA) of the knee poses a significant burden on physical mobility and quality of life, especially in middle-aged adults. This study evaluates the outcomes of a modified fourth-generation autologous cartilage transplantation technique developed to overcome limitations of traditional cartilage repair strategies. The major learning curve observed during this study was that patient preferred a minimally invasive and a shorter hospital stay technique over traditional TKR. The case series involves a cohort of 15 patients with Grade 2-3 knee OA, the case series showed significant improvements in pain relief, knee function, early mobilization, and patient satisfaction with no reported adverse events. Some patients had follow-up data extending up to 5 years, with results consistent with 6-month outcomes. Improved patient mobility score and improved patient satisfaction score noted. This technique offers a cost-effective, single-stage, arthroscopic alternative with promising short- and mid-term outcomes. Thus, this technique caters to the population at early osteoarthritis stage preventing an Early replacement.